2019
DOI: 10.3390/jsan8010004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Multi-Sensor Technology for Enhancing Global Security in Closed Environments Using Cloud-Based Resources

Abstract: By nature, some jobs are always in closed environments and employees may stay for long periods. This is the case for many professional activities such as military watch tours of borders, civilian buildings and facilities that need efficient control processes. The role assigned to personnel in such environments is usually sensitive and of high importance, especially in terms of security and protection. With this in mind, we proposed in our research a novel approach using multi-sensor technology to monitor many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It is necessary to mention that the present research has shown an alternative for neutron detection for nuclear safety and security systems, prioritizing the possible implementations seizing the advantages of the IoT. IoT-based systems provide elements to configure and implement multisensor networks for location and tracking items [43], and these (multisensor-based tracking systems) are widely enhanced by cloudbased resources [44].…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary to mention that the present research has shown an alternative for neutron detection for nuclear safety and security systems, prioritizing the possible implementations seizing the advantages of the IoT. IoT-based systems provide elements to configure and implement multisensor networks for location and tracking items [43], and these (multisensor-based tracking systems) are widely enhanced by cloudbased resources [44].…”
Section: Resultsmentioning
confidence: 99%
“…OSEMA supports multiple sensor models, application layer protocols, and data formats to enable interoperability, which is highly recommended in a multi-sensor context [56]. In addition, it offers a REST API, which further extends the versatility of the manager.…”
Section: Use Cases Of Osemamentioning
confidence: 99%